1994
DOI: 10.1073/pnas.91.13.5784
|View full text |Cite
|
Sign up to set email alerts
|

The neuroendocrine polypeptide 7B2 is an endogenous inhibitor of prohormone convertase PC2.

Abstract: The subtilisin-like prohormone convertase PC2 and the polypeptide 7B2 (an intracellularly cleaved protein of unknown function) are both selectively present in the regulated secretory pathway of neurons and endocrine cells.Here we demonstrate that intact recombinant 7B2 is a potent inhibitor of PC2 and prevents proPC2 cleavage in vitro, whereas the 7B2 cleavage product is virtually inactive. The PC2-related proteinase PC1/PC3 is not inhibited by 7B2.Furthermore, the carboxyl-terminal half of the 7B2 protein seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
126
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(132 citation statements)
references
References 32 publications
6
126
0
Order By: Relevance
“…Inhibition of PC2 by the 7B2 CT peptide strongly depends on the presence of a K-K site (40,42); other residues within the peptide are also critical to inhibitory potency (44). No information is available thus far on which PC2 residues confer the ability to be inhibited by the CT peptide; presumably, these residues are not shared by PC1, which is not inhibited by this peptide (45).…”
mentioning
confidence: 99%
“…Inhibition of PC2 by the 7B2 CT peptide strongly depends on the presence of a K-K site (40,42); other residues within the peptide are also critical to inhibitory potency (44). No information is available thus far on which PC2 residues confer the ability to be inhibited by the CT peptide; presumably, these residues are not shared by PC1, which is not inhibited by this peptide (45).…”
mentioning
confidence: 99%
“…1A, lane 6). Intact 7B2 has been shown to act as a specific inhibitor of prohormone convertase PC2 in an in vitro enzyme assay [24]. Incubation of the lysate in the presence of both processed and intact 7B2 (both at-1 pM) also led to a complete block of POMC conversion, indicating that the intact form of 7B2 can abolish the stimulating effect of the processed form ( Fig.…”
Section: Effect Of Recombinant 7b2 On Pomc Conversion Inmentioning
confidence: 87%
“…Production and purification of the recombinant proteins was performed as described previously [24]. Recombinant intact 7B2 (amino acid residues 1-185; numbering refers to [26]), processed 7B2 (residues 1-151), the C-terminally truncated 7B2 mutants pNK171 (1-171), pNF177 (1-177), pNG162 (1-162), pNP131 (1 131), and pNG86 (1 86), and the N-terminally truncated 7B2 mutants pCP93 (93-185) and pCD125 (125-185) were used in the present study.…”
Section: Recombinant 7b2 Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…3) which revealed that only PACE4-A could be detected in the medium. In order to further probe the intracellular enzymatic activity of either PACE4-A or PACE4-CS, we co-expressed these isoforms with pro7B2, a PC2-specific binding protein [20,28,29] known to be processed in the TGN by furin-like enzymes [20,30]. As shown in Fig.…”
Section: Processing Of Pro7b2 By Pace4-a and Pace4-csmentioning
confidence: 99%